PENINGKATAN KUAT LENTUR BETON FAST TRACK MUTU FS 45 DENGAN ADMIXTURE MR 73 - FAISAL BURHANNUDIN; YUSUF ALI; Yosafat Damar Wicaksono; Rida Handiana Devi (Politeknik Negeri Semarang, 2025)
A number of studies and concrete trials have been undertaken in an effort to improve the quality of concrete and address common issues in the construction industry, such as project deadlines. Efforts that have been made to improve the quality of concrete include modifying the strength of high concrete at 7 days of age using chemical admixtures. This research aims to determine the effect of the MR 73 admixture on the flexural strength of concrete at 7 and 28 days of age. The research method used is quantitative experimentation. The research results show that concrete with an admixture of MR 73 at a dosage of 0.4% at 7 days of age has an average flexural strength of 43.5042 kg/cm ², while normal concrete at the same age has a flexural strength of 35.34 kg/cm ². At 28 days of age, concrete with an admixture of MR 73 at a dosage of 0.4% reaches an average flexural strength of 49.97 kg/cm ², compared to normal concrete which reaches 45.54 kg/cm ². The MR 73 admixture has been proven to increase the flexural strength of concrete by 23% at 7 days and by 10% at 28 days compared to normal concrete.